Improving the Mie GACOAN Online Food Ordering Application Using the System Usability Scale (SUS) - Sarungu, Cornelius Mellino; Hatrinidinar Rasya, Raihannissa; Devina Tiara Maharani, Denta; Alfianto, Royan (ULTIMA InfoSys, 2025)
Improvement of the online food ordering application through the System Usability Scale (SUS) method to enhance user satisfaction and streamline the ordering process. Driven by the rapid expansion of online food ordering in Indonesia, this study aims to address long queues and improve customer convenience through optimized digital solutions. Current challenges include delayed ordering processes and limitations in existing application features, such as navigation issues, unclear language, and limited ordering options for dine-in, takeaway, and delivery. The research employs a mixed-methods approach, combining survey and interview data with competitive analysis, to identify critical areas for enhancement. Design improvements focus on user interface (UI) and user experience (UX) to simplify navigation, optimize payment processes, and make language more user-friendly. Initial usability tests resulted in a SUS score of 48, categorizing the application as "poor." After iterative improvements based on Agile Development, the score rose to 70, indicating an "acceptable" level of usability. This research highlights the importance of continuous UI/UX refinement to meet consumer expectations, with recommendations for ongoing updates and professional design involvement to maintain and enhance app performance. Findings suggest that improving usability and functionality can significantly elevate customer satisfaction, positioning online food ordering competitively within the digital food service sector.